2023
DOI: 10.3390/v15020541
|View full text |Cite
|
Sign up to set email alerts
|

A Capsid Protein Fragment of a Fusagra-like Virus Found in Carica papaya Latex Interacts with the 50S Ribosomal Protein L17

Abstract: Papaya sticky disease is caused by the association of a fusagra-like and an umbra-like virus, named papaya meleira virus (PMeV) and papaya meleira virus 2 (PMeV2), respectively. Both viral genomes are encapsidated in particles formed by the PMeV ORF1 product, which has the potential to encode a protein with 1563 amino acids (aa). However, the structural components of the viral capsid are unknown. To characterize the structural proteins of PMeV and PMeV2, virions were purified from Carica papaya latex. SDS-PAGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The interactions between the PMeV complex and papaya plants have not been characterized in detail, but it is known that the viruses are located primarily, if not solely, in cells of the laticiferous vessels, responsible for storing latex and having a predominance of proteases. In an attempt to escape the viral attack, papaya cells activate defense mechanisms before the flowering period, altering the expression of genes related to the synthesis of growth regulators and encoding proteins related to the chloroplast [49]. The study also demonstrated that two regions of the putative CP ORF of PMeV-1, CP2 and CP4, interact with ribosomal proteins, specifically the 50S ribosomal protein L17 (RPL17).…”
Section: Papayamentioning
confidence: 92%
“…The interactions between the PMeV complex and papaya plants have not been characterized in detail, but it is known that the viruses are located primarily, if not solely, in cells of the laticiferous vessels, responsible for storing latex and having a predominance of proteases. In an attempt to escape the viral attack, papaya cells activate defense mechanisms before the flowering period, altering the expression of genes related to the synthesis of growth regulators and encoding proteins related to the chloroplast [49]. The study also demonstrated that two regions of the putative CP ORF of PMeV-1, CP2 and CP4, interact with ribosomal proteins, specifically the 50S ribosomal protein L17 (RPL17).…”
Section: Papayamentioning
confidence: 92%
“…This domain is a signature feature of reoviruses and other dsRNA viruses, comprising a protein family of viral core proteins with nucleic acid binding activity [1]. Although fusagraviruses are commonly associated with fungal hosts, PMeV -a previously-considered totivirus associated with papaya sticky disease (PSD)-has recently been considered a potential member of the fusagraviridae [2,3]. Papaya (Carica papaya L.) is a dicotyledonous plant belonging to Caricaceae family.…”
Section: Full Textmentioning
confidence: 99%
“…PMeV is an 8.7 kbp double-stranded RNA (dsRNA) virus ( Fusagraviridae ) [ 81 ] that, on co-infection with PMeV2, a 4.5 kbp single-stranded RNA (ssRNA) (umbra-like virus) [ 36 ], causes papaya sticky disease (PSD) [ 36 , 82 ]. Sequence similarity and phylogenetic analysis that included PMeV2, PMeV-Mx, and PpVQ suggest that these viruses may be different isolates from the same umbravirus [ 36 ].…”
Section: Papaya Meleira Virus Complex: Two Viruses Infecting Laticifersmentioning
confidence: 99%
“…It is also capable of endogenous mRNA transcription within an intact virus particle using viral-encoded enzymes [ 87 ]. Although PMeV complex particles have been isolated and their genome and structural proteins have been studied [ 81 ], how C. papaya latex components influence PMeV/PMeV2 replication and effects on the plant’s laticifers remains largely unknown.…”
Section: Papaya Meleira Virus Complex: Two Viruses Infecting Laticifersmentioning
confidence: 99%